Pengaruh Produk Domestik Bruto(PDB), Inflasi dan Kurs Dollar Terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia - Konstantia, Nuryantiwi B1021151093 (Jurnal Manajemen Update, 2019)
ABSTRACT This study aims to examine and analyze the effect of Gross Domestic Product (GDP), Dollar Exchange Rate and Inflation on the Composite Stock Price Index (CSPI) on the Indonesia Stock Exchange in the period 2007-2017. This research was conducted with a quantitative approach. The population in this study is time series data which includes the Composite Stock Price Index (CSPI), Gross Domestic Product (GDP), inflation and the dollar exchange rate. The total sample is 44 samples which include timeseries Composite Stock Price Index (CSPI), Gross Domestic Product (GDP), inflation and the dollar exchange rate, then the data analysis uses time series regression and hypothesis testing. The results showed that Gross Domestic Product (GDP) and Inflation had no significant negative effect on the Composite Stock Price Index (CSPI), while the dollar exchange rate had a positive positive effect on the Composite Stock Price Index (CSPI). In the test of the coefficient of determination (R2), the Composite Stock Price Index (CSPI) is influenced by the variable Gross Domestic Product (GDP), inflation and the dollar exchange rate of 45.2776 percent, while the remaining 54.7224 percent is influenced by other variables not examined in this research Keywords: Gross Domestic Product (GDP), dollar exchange rate, inflation and the Composite Stock Price Index (CSPI).Daftar PustakaArif, Dodi. (2014). Pengaruh Produk Domestik Bruto, Jumlah Uang Beredar (JUB), Inflasi dan BI Rate terhadap Indeks Harga Saham Gabungan di Indonesia periode 2007-2013. Jurnal Ekonomi Bisnis Volume 19 No. 3, Desember 2014, hal 63-77, Universitas Gunadharma, Depok, Indonesia.Eiteman, David K., Arthur I. Stonehill, and Michael H. Moffett. (2010). Multinational Business Finance. Twelfth Edition (International Edition). Global Edition Pearson.George, J. M., G. R. Jones. (2002). Understanding and Managing Organizational Behavior. New Jersey: Prentice HallHarsono, A.R. & Worokinasih.S. (2018). Pengaruh Inflasi, Suku Bunga dan Nilai Tukar Rupiah Terhadap Indeks Harga Saham Gabungan (Studi Pada Bursa Efek Indonesia periode 2013-2017), Jurnal Artikel Bisnis (JAB), Vol 60, No. 2 Juli 2018, hal 102-110, Universitas Brawijaya, Malang, Indonesia.Haryanto, B.A.M. (2017). Analisis Pengaruh Foreign Inflow, Inflasi, Suku Bunga dan Kurs pada Return Saham (Studi pada Sektor Keuangan Periode Juli  2016-Januari 2017), Journal Of Management, Vol 6, No.2 Tahun 2017,hal 1-11, Universitas Diponegoro, Semarang, Indonesia.Herlambang, Tedy. (2002). Ekonomi Makro: Teori, Analisis ,dan Kebijakan. Jakarta: PT Gramedia Pustaka Utama.Karim, Adiwarman A. (2015). Ekonomi Makro Islam Ed 3, Cet 8. Jakarta: Rajawali Pers.Ilmi, M.F. (2017). Pengaruh Nilai Tukar Rupiah, Inflasi dan Tingkat Suku Bunga SBI Terhadap Indeks Harga Saham LQ-45 Periode Tahun 2009- 2013, Jurnal Nominal, Vol 6, No.1, Tahun 2017, hal 93-108, Universitas Negeri Yogyakarta, Indonesia.Indriyo dan Basri. (2002). Manajemen Keuangan, Edisi 4. Yogyakarta: BPFE.Kewal, S.S. (2012). Pengaruh Inflasi, Suku Bunga, Kurs dan Pertumbuhan  Produk Domestik Bruto Terhadap Indeks Harga Saham Gabungan, Jurnal Economia, Volume 8, Nomor 1, April 2012, hal 53-64, STIE Musi Palembang, IndonesiaLatumaerissa, Julius R. (2011). Bank dan Lembaga Keuagan Lain. Jakarta: Salemba EmpatMankiw, N. Gregory. (2007). Makroekonomi, Edisi Keenam. Jakarta: Penerbit Erlangga.Mangkoesoebroto, Guritno, (2003). Ekonomi Publik, Edisi Keempat, Yogyakarta: Penerbit BPFE UGM.Mardayanti, U & Rosalina, A. (2013). Analisis Pengaruh Nilai Tukar, Tingkat Suku Bunga dan Inflasi Terhadap Indeks Harga Saham Studi Kasus Pada Perusahaan Properti yang Terdaftar di Bursa Efek Indonesia, Jurnal Riset Manajemen Sains Indonesia (JRMSI), Vol 4, No. 1, 2013, hal 1-15, Universitas Negeri Jakarta, Indonesia.Nurwani (2016). Analisis Pengaruh Inflasi, Nilai Tukar Rupiah dan Suku Bunga SBI Terhadap Pergerakan Indeks Harga Saham Gabungan di Bursa Efek Indonesia, Universitas Muhammadiyah Sumatera Utara, Indonesia.Putri, N.M.A.A.S., Suzan, L. & Mahardika,D.P.K (2016). Pengaruh Harga Emas Dunia dan Nilai Tukar Rupiah Dollar Terhadap Indeks Harga Saham Gabungan (Studi Kasus Pada Bursa Efek Indonesia Periode 2010-2014), e-proceeding of management,Vol 3, No 2 Agustus 2016, hal 1612-1618, Universitas Telkom, Bandung, Indonesia.Rahardja, Prathama. Manurung, Mandala. (2008). Pengantar Ilmu Ekonomi (Mikroekonomi dan Makroekonomi), Edisi Ketiga, Jakarta; Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.Sukirno, Sadono. (1999). Pengantar Teori Makroekonomi. Jakarta. PT. Raja Grafindo Perseda.Sukirno, Sadono. (2000). Makroekonomi Modern. Jakarta: PT Raja Grafindo Persada.Sukirno, Sadono. (2004). Pengantar Teori Makroekonomi.: Jakarta.  PT Raja Grafindo Persada.Sukirno, Sadono. (2011). Makro Ekonomi Teori Pengantar Edisi Ketiga. Jakarta.  Rajawali Pers.Sugiyono. (2013). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sunariyah. (2003). Pengetahuan Pasar Modal. Edisi Ketiga. Yogyakarta: Unit Penerbit dan Percetakan (UMP) AMP YKPN.Suprihati (2015). The Analysis of The Influence of Exchange Rate, SBI Interest Rate, Inflation Rate, Dow Jones Index And Nikkei 225 Index To IHSG, International Journal Of Scientific Research And Education, Vol.3 Issue 5, May 2015, pages 3428-3442, STIE AAS, Surakarta, Indonesia.Tandelilin, Eduardus. (2010). Portofolio dan Investasi: Teori dan Aplikasi. Edisi Pertama. Yogyakarta: Kanisius.Widyasa, V.I.A. & Worokinasih, S. (2018). Pengaruh Tingkat Inflasi, Nilai Tukar Rupiah dan Tingkat Suku Bunga Domestik Terhadap Indeks Saham Syariah Indonesia (ISSI) (Studi Pada Saham Syariah Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017), Jurnal Artikel Bisnis (JAB), Vol 60, No. 1 Juli 2018, hal 119-128, Universitas Brawijaya, Malang, Indonesia.Yunita, Nurlita.E. & Robiyanto (2018). Pengaruh Suku Bunga, Kurs Rupiah dan Harga Emas Terhadap Return Harga Saham Sektor Pertambangan di Bursa Efek Indonesia, Prosiding Sendi- U 2018, hal 624-630, Universitas Kristen Satya Wacana, Salatiga, Indonesia.finance.yahoo.com.https://forzanapoli777.blogspot.com/2015/09/teori-makro-pengeluaran-pemerintah_20.htmlhttp://khudaifimedia.blogspot.com/2016/09/teori-nilai-uang-menurut-irving fisher.html.www.bi.go.id.www.bps.go.id.www.idx.co.id.